Peran Orang Tua dan Guru dalam Mengembangkan Pendidikan Islam Peserta Didik di Era Digital - Fathoni, Mokh Shoiful; Arifin, Muhammad Bustanul; Ilham PL, Muhammad Asfani (Social Science Academic, 2024)
Islamic education for students is not only a duty but also a moral responsibility in shaping a generation that is spiritually and morally strong amid changing times. In the digital era, characterized by the rapid advancement of information technology, Islamic education faces significant challenges. The younger generation has instant access to information from various sources that do not always align with Islamic values. The role of parents and teachers becomes increasingly crucial in managing children's use of technology and integrating Islamic values into daily life. This research aims to understand the critical role of parents and teachers in developing Islamic education for students in the digital age. Using a library research approach, this study identifies the challenges faced and effective strategies that can be applied to ensure that Islamic education remains relevant. The findings indicate that integrating technology into teaching methods and active supervision by parents are essential. Parents and teachers must collaborate to create a learning environment that supports Islamic values, both at home and at school. This research provides practical guidelines for educators, parents, and policymakers to optimize their roles in supporting sustainable Islamic education in the digital era.